Efficacy and safety of statin use in children and adolescents with familial hypercholesterolaemia: a systematic review and meta-analysis of randomized-controlled trials - Anagnostis, Panagiotis; Vaitsi, Konstantina; Kleitsioti, Panagiota; Mantsiou, Chrysanthi; Pavlogiannis, Konstantinos; Athyros, Vasilios G.; Mikhailidis, Dimitri P.; Goulis, Dimitrios G. (Endocrine, 2020)
Purpose Statins are the mainstay of treatment for patients with familial hypercholesterolaemia (FH). However, their efficacy and safety in children and adolescents with FH has not been well-documented. The purpose of this study was to systematically investigate and meta-analyze the best available evidence from randomized-controlled trials (RCTs) regarding the efficacy and safety of statins in this population. Methods A comprehensive search was conducted in PubMed, Scopus and Cochrane, up to 10 January 2020. Data were expressed as mean differences with 95% confidence intervals (CI). The I 2 index was employed for heterogeneity. Results Ten RCTs were included in the qualitative and quantitative analysis (1191 patients, aged 13.3 ± 2.5 years). Compared with placebo, statins led to a mean relative reduction in total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), triglyceride and apolipoprotein B (apo-B) concentrations by −25.5% (95% CI −30.4%, −20.5%; I 2 91%), −33.8% (95% CI −40.1%, −27.4%; I 2 90%), −8.4% (95% CI −14.8%, −2.03%; I 2 26%) and −28.8% (95% CI −33.9%, −23.6%; I 2 83%), respectively. High-density lipoprotein cholesterol (HDL-C) was increased by 3.1% (95% CI 1.1%−5.2%; I 2 0%). Statins were well-tolerated, with no significant differences in transaminase and creatine kinase levels or other adverse effects compared with placebo. Statins exerted no effect on growth or sexual development. Conclusion Statins are quite effective in reducing TC, LDL-C, TG and apo-B and increasing HDL-C concentrations in children and adolescents with FH. No safety issues were seen with statin use.